2009
DOI: 10.1073/pnas.0901575106
|View full text |Cite
|
Sign up to set email alerts
|

The canonical pathway for selenocysteine insertion is dispensable in Trypanosomes

Abstract: The micronutrient selenium is found in proteins as selenocysteine (Sec), the 21st amino acid cotranslationally inserted in response to a UGA codon. In vitro studies in archaea and mouse showed that Sec-tRNA Sec formation is a 3-step process starting with serylation of tRNA Sec by seryl-tRNA synthetase (SerRS), phosphorylation of serine to form phosphoserine (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…75 Se labeling studies carried out with wild-type and LdSepSecS null mutants helped in ascertaining a role for LdSepSecS in selenoprotein synthesis in Leishmania as no selenoproteins could be detected in the lysate of the null mutant parasites. This is consistent with earlier studies in Trypanosome where the presence of the three selenoproteins corresponding to the predicted molecular masses of the kinetoplastid homologs, SelK (9.5 kDa), SelT (28.8 kDa), and SelTryp (89 kDa) have been reported (10,12). Cassago et al (11) had earlier reported that the genes for glutathione peroxidase, selenoprotein R and selenoprotein SPS2 homologues in Leishmania have evolved into nonselenium-containing proteins.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…75 Se labeling studies carried out with wild-type and LdSepSecS null mutants helped in ascertaining a role for LdSepSecS in selenoprotein synthesis in Leishmania as no selenoproteins could be detected in the lysate of the null mutant parasites. This is consistent with earlier studies in Trypanosome where the presence of the three selenoproteins corresponding to the predicted molecular masses of the kinetoplastid homologs, SelK (9.5 kDa), SelT (28.8 kDa), and SelTryp (89 kDa) have been reported (10,12). Cassago et al (11) had earlier reported that the genes for glutathione peroxidase, selenoprotein R and selenoprotein SPS2 homologues in Leishmania have evolved into nonselenium-containing proteins.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been previously reported in case of T. brucei, where the pathway for selenocysteine insertion was found to be dispensable (10,42).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The insertion of selenium into Sec-dependent enzymes requires the formation of a highly reactive reduced selenium donor compound monoselenophosphate. Monoselenophosphate synthesis is catalyzed by SPS in a 1:1 ratio from selenide and ATP [5,[15][16][17].…”
Section: Specific Characteristics Of Kinetoplas-tid Selenocysteine Bimentioning
confidence: 99%